The Status, Trends, and Limitations of Philippine Mollusk Production and Trade Based on Available Databases and Publications - Ordinario, John Alberto H; Anticamara, Jonathan A. (Journal of Tropical Biodiversity and Biotechnology, 2023)
Mollusk trade is vital in many coastal areas and island communities throughout the Philippines because it provides livelihoods, food, and incomes to millions of Filipinos via fisheries (e.g., shellfish fishing and gleaning), shell craft, arts, shell trading and collections, and aquaculture. However, the assessments of the national trends and status of mollusc production and trade in the Philippines are largely non-existent in peer-reviewed literature. The main purpose of this paper is to present and evaluate the status and trends of traded Mollusks in the Philippines based on available online databases and a systematic review of published literature. To date, available databases on Philippine mollusk trade showed an initial increase in traded volume (the 1970s to 2006) but decreased afterward. In contrast, the traded mollusk value continued to generally increase over time (albeit the observed decrease between 2011 and 2016), indicating value increase as mollusk volume decreased. However, there is a great need to (1) resolve many of the obvious inconsistencies in data entries across all the available mollusk trade databases (BFAR, PSA, and CITES) and (2) provide field assessment of the Philippine mollusk trade and the conservation status of all traded mollusk taxa in the country.